Incorporation of Various Nanoclays in Semi-refined Carrageenan Film Composite. Issue 1 (November 2021) - Sedayu, B B; Fransiska, D; Wullandari, P; Novianto, T D; Handoyo, W T; Assadad, L
Abstract: In current investigation, various commercial nanoclays with different level of hydrophilicity i.e., hydrophilic bentonite (HB), cloisite 10A, and cloisite® 30B were incorporated to a hydrophilic semi-refined carrageenan (SRC) films to observe their presence in film matrix in regards with the final film's properties. High shear mixing and sonication were applied to the film preparation to obtain high dispersion of nanoclays in the matrix. As expected, the hydrophilic clay showed better dispersion within the matrix as shown in Energy Dispersive X-Ray Spectroscopy (EDS) image. The more hydrophilic clay inclusion resulted in higher tensile strength, while the more hydrophobic resulted in higher stiffness of the films. The water vapour permeability was decreased in corresponded to the more hydrophobic clay incorporated, and the thermal properties of the films were overall enhanced by the nanoclays reinforcement. In general, nanoclays incorporation in SRC film improved the overall properties of the SRC film.